Amino acid composition and antioxidant properties of the enzymatic hydrolysate of calabash nutmeg (Monodora myristica) and its membrane ultrafiltration peptide fractions. Issue 3 (14th August 2020) - Akinyede, Adedamola I.; Fagbemi, Tayo N.; Osundahunsi, Oluwatooyin F.; Aluko, Rotimi E.
Abstract: The aim of this work was to determine amino acid composition and in vitro antioxidant activities of Monodora myristica protein hydrolysate and its membrane ultrafiltration peptide fractions. The Alcalase hydrolysate was fractionated using ultrafiltration membranes to produce peptide sizes of <1, 1–3, 3–5, and 5–10 kDa. The results showed that sequential fractionation resulted in higher glycine and glutamic acid and glutamine contents. Analysis of in vitro antioxidant properties showed that fractionation of the M. myristica hydrolysate led to significant ( p < .05) improvements in 2, 2‐diphenyl‐1‐picrylhydrazyl radical scavenging, metal chelation activity, ferric reducing antioxidant power (FRAP), and hydroxyl (OH) radical scavenging activity. Linoleic acid oxidation was significantly ( p < .05) attenuated by the peptide fractions. We conclude that peptide antioxidant activities were significantly ( p < .05) improved by membrane fractionation, especially the 3–5 kDa fraction. Practical applications: The use of protein hydrolysate fractions with potential to prevent oxidation, which can reduce shelf life of foods and cause degenerate diseases due to cell damage is proposed for Monodora myristica . The demand for natural products and negative health issues associated with artificial food ingredients have led to increased consumer preference for natural sources of antioxidants. The protein hydrolysate and membrane fractions produced in this work showed high antioxidant ability that could qualify them to replace toxic synthetic antioxidants in foods. Peptide fractions had better metal chelation than the hydrolysates, which is important because chelation of metal ions can decrease the amount of free iron available to participate in the Fenton reaction and ultimately decrease the formation of toxic free radicals. Incorporation of the peptides into foods will enhance scavenging of toxic free radicals that may form during storage, thereby improving product freshness and shelf life in addition to preventing human degenerative diseases. Abstract : Findings has shown that alcalase produced Monodora myristica hydrolysate (MMH) and its peptide fractions possess the ability to scavenge free radicals, chelate metal ions and inhibit linoleic acid oxidation. The 3–5 kDa exhibited highest content of hydrophobic and aromatic amino acids which may have potential for preventing oxidative degradation of foods during handling and storage. The effectiveness of MMH and fractionated peptides against linoleic acid oxidation suggests that these products could have potential roles as antioxidants against chronic diseases.